Faktor-faktor yang Berhubungan dengan Pengeluaran Pangan Hewani pada Rumah Tangga Indonesia: Faktor-Faktor yang Berhubungan dengan Pengeluaran Pangan Hewani pada Rumah Tangga Indonesia - Mauludyani, Anna Vipta Resti; Syafiq, Ahmad (Universitas Airlangga, 2023)
Background: Eating animal protein (AP) can prevent stunting in children under five, which currently is still 21.5%. Due to scarce resources, households had trouble distributing the cost and frequently had to choose between it and other food expenses. Objectives: This study aimed to examine the relationship between various food expenditures and expenditure on AP among Indonesian households. Methods: This was a cross-sectional study using secondary data. Data on household food expenditures on AP, prepared food and beverage, cereals, instant noodles, fruits, cooking oil, cigarette, and sugar, total expenditure, household size, and age and education of household head from 97,467 household samples with children under five were obtained from the National Socioeconomic Survey (Susenas) March 2018. Susenas data were collected through interviews using a structured questionnaire. Using IBM SPSS Version 22, a multiple linear regression was carried out, adjusted for household socioeconomic factors. Results: The average per-capita household expenditure on AP was IDR 24,912, contributing 4.72% to total food expenditure. This expenditure was higher than that on cereals (3.77%) but lower than that on prepared foods and beverages (6.15%). There was a positive association (p<0.001) between fruits, instant noodles, cooking oil, sugar, and beans and nuts expenditure and AP expenditure. Contrarily, there was an inverse relationship between prepared food and beverage (p<0.001), cereals (p=0.004), and cigarette expenditure (p<0.001) and animal protein expenditure. Conclusions: The amount spent on animal proteins was positively correlated with other food. It is possible that the consumption of animal proteins would increase if household funds were diverted from cigarettes and prepared food and beverage.